Effectiveness of a biopsychosocial e-learning intervention on the clinical judgements of medical students and GP trainees regarding future risk of disability in patients with chronic lower back pain: study protocol for a randomised controlled trial. Issue 5 (26th May 2016) - Dwyer, Christopher P; Durand, Hannah; MacNeela, Pádraig; Reynolds, Bronagh; Hamm, Robert M; Main, Christopher J; O'Connor, Laura L; Conneely, Sinéad; Taheny, Darragh; Slattery, Brian W; O'Neill, Ciaran; NicGabhainn, Saoirse; et al.
Abstract : Introduction: Chronic lower back pain (CLBP) is a major healthcare problem with wide ranging effects. It is a priority for appropriate management of CLBP to get individuals back to work as early as possible. Interventions that identify biopsychosocial barriers to recovery have been observed to lead to successfully reduced pain-related work absences and increased return to work for individuals with CLBP. Modern conceptualisations of pain adopt a biopsychosocial approach, such as the flags approach. Biopsychosocial perspectives have been applied to judgements about future adjustment, recovery from pain and risk of long-term disability; and provide a helpful model for understanding the importance of contextual interactions between psychosocial and biological variables in the experience of pain. Medical students and general practitioner (GP) trainees are important groups to target with education about biopsychosocial conceptualisations of pain and related clinical implications. Aim: The current study will compare the effects of an e-learning intervention that focuses on a biopsychosocial model of pain, on the clinical judgements of medical students and trainees. Methods and analysis: Medical student and GP trainee participants will be randomised to 1 of 2 study conditions: (1) a 20 min e-learning intervention focused on the fundamentals of the flags approach to clinical judgement-making regarding risk of future pain-related disability; compared with a (2) wait-list control group on judgement accuracy and weighting (ie, primary outcomes); flags approach knowledge, attitudes and beliefs towards pain, judgement speed and empathy (ie, secondary outcomes). Participants will be assessed at preintervention and postintervention. Ethics and dissemination: The study will be performed in agreement with the Declaration of Helsinki and is approved by the National University of Ireland Galway Research Ethics Committee. The results of the trial will be published according to the CONSORT statement and will be presented at conferences and reported in peer-reviewed journals. Trial registration number: ISRCTN53670726; Pre-results.